Exploring the Sociodemographic Characteristics and Staple Food Consumption Patterns of Low-Income People in Kendari City, Indonesia - Sitti Aida Adha Taridala; Dwi Rinnarsari Noraduola; La Ode Muhammad Golok Jaya; Arsy Aysyah Anas; Azzahra Miftahul Firdausah (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
The city's attractiveness encourages urbanization, namely the movement of people from rural to urban areas. Urbanization accompanied by a transition to diet will significantly impact the food system. This study aims to analyze low-income people's sociodemographic characteristics and consumption patterns. This research was conducted in Kendari City. Data collection was carried out in October-November 2021. Determining the research location began by selecting densely populated residential areas in Kendari City. Based on the Geographic Information System (GIS) results, dense residential blocks were obtained in Mandonga District, namely several Neighborhood Units (RT) in Korumba Village and residential blocks in several RTs in Petoaha Village, Abeli District, which are on the coast of Kendari Bay. The low-income people (LIP) population was obtained from data on Social Assistance recipients in each sample village. The total sample is 20% of the population, covering 194 household respondents and extracting data and information using a combination of the food recall and weighing methods. The variables in this study are sociodemographic characteristics, including age, education, number of family members, and gender; house and Yard, as well as variables related to food sources of carbohydrates consumed by MBR households in the last 3 (three) days, including the type, quantity, price, and expenditure of food. Data analysis was carried out in a qualitative descriptive manner, with cross-tabulations and percentages. The results showed that the respondents were at an average age of 44.91 years, the length of schooling was 8.27 years, the number of family members was 4 (four), and most were women, reaching 150 people. Most respondents have houses made of planks (wood), namely 97 people, with yards that have not been fully utilized for agricultural activities. The staple food consumption pattern of the respondent's family is dominated by rice (0.48 kg), and the amount of consumption of sago and cassava is minimal, only 0.07 kg and 0.05 kg, respectively. The most significant expenditure for food sources of carbohydrates is to buy rice, which is IDR 4,756/day. Therefore, policies are needed to encourage urban agricultural activities and revitalize the utilization of non-rice staple foods. Need to be disseminated. One form is not assisting in the form of rice to LIP when there is a government assistance program.